Singled Out: Invisibilization of Single Mothers in Social Welfare and Protection Policies - Queenie Pearl Villalon Tomaro; Lynrose Jane Genon; Al-Farouk Amod; Perla P Palomares (Jurnal Studi Pemerintahan, 2021)
In the context of Southeast Asia, data on the experiences and circumstances of single mothers are sparse. Single mothers continue to experience stereotypes, discrimination, exclusion from welfare policies and invisibilization of compounding burdens they carry. This study is a literature mapping of scholarly works on single mothers and welfare policies for single mothers and their families. We seek to highlight single mother’s experience as inputs for a more gender- and needs-responsive policy making process. Findings of the study reveal that the majority of Southeast Asian countries have apparent social welfare policies for single mothers except Laos and Indonesia. Common programmes for single mothers include entrepreneurship capacity and financial aid. A two-pronged approach for Southeast Asian Countries which incorporates accessible childcare services and vocational training programs is recommended to achieve more promising outcomes for single mothers.